2017
DOI: 10.1007/s00265-017-2397-y
|View full text |Cite
|
Sign up to set email alerts
|

Vocal foragers and silent crowds: context-dependent vocal variation in Northeast Atlantic long-finned pilot whales

Abstract: Vocalisations form a key component of the social interactions and foraging behaviour of toothed whales. We investigated changes in calling and echolocation behaviour of long-finned pilot whales between foraging and non-foraging periods, by combining acoustic recordings and diving depth data from tagged individuals with concurrent surface observations on social behaviour of their group. The pilot whales showed marked vocal variation, specific to foraging and social context. During periods of foraging, pilot wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…The consistently high diving and vocal coordination demonstrated by both tagged whale pairs and individually tagged whales within groups, covering two species and different geographical areas, strongly suggest that collective behaviour is critical for social beaked whale groups: although the obligate deep vocal foraging intervals put beaked whales at risk of detection and stalking by killer whales performing passive acoustic tracking, beaked whales are safe to vocalize while in their deep refuge and their collective diving behaviour frees them from the need to vocalize during ascents to re-join non-diving members at the surface. This is in contrast to pilot whales or sperm whales that often vocalize during ascents to mediate group reunion acoustically [10][11][12][13] . That beaked whales of different genera (Mesoplodon, Ziphius) show the same coordinated behaviour suggests that the coordination of diving and vocal activity in social groups may have evolved millions of years ago or has had sufficient evolutionary value as to drive convergence towards a strikingly similar strategy.…”
Section: Resultsmentioning
confidence: 99%
“…The consistently high diving and vocal coordination demonstrated by both tagged whale pairs and individually tagged whales within groups, covering two species and different geographical areas, strongly suggest that collective behaviour is critical for social beaked whale groups: although the obligate deep vocal foraging intervals put beaked whales at risk of detection and stalking by killer whales performing passive acoustic tracking, beaked whales are safe to vocalize while in their deep refuge and their collective diving behaviour frees them from the need to vocalize during ascents to re-join non-diving members at the surface. This is in contrast to pilot whales or sperm whales that often vocalize during ascents to mediate group reunion acoustically [10][11][12][13] . That beaked whales of different genera (Mesoplodon, Ziphius) show the same coordinated behaviour suggests that the coordination of diving and vocal activity in social groups may have evolved millions of years ago or has had sufficient evolutionary value as to drive convergence towards a strikingly similar strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Class-16 ( Fig. 2p), a complex vocalisation that comprised three successive parts, was almost identical to 'two inflected calls with click series component' from northeast Atlantic long-finned pilot whales 37 . Both vocalisations showed similar components, contours, durations, and frequencies, although the northeast Atlantic vocalisation ended in a downsweep rather than a plateau.…”
Section: Percentage Of Callsmentioning
confidence: 93%
“…Population estimates of long-finned pilot whales in the southern hemisphere do not exist 32 , 34 . The acoustic repertoire of northern hemisphere long-finned pilot whales has been described as highly diverse, repetitive, and physically complex 19 , 35 37 . To date, no data have been reported on long-finned pilot whale sound usage in the southern hemisphere 6 .…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed that these were foraging dives, targeting a time that vertically migrating prey become more readily available as they move closer to the surface. Visser et al [70] found that LFPWs produce more calls during foraging than non-foraging periods, with increased vocalisations potentially indicative of mediating spacing between group members or synchronisation of foraging activity.…”
Section: Discussionmentioning
confidence: 99%